PELATIHAN PEMBELAJARAN DALAM KONSEP KURIKULUM MERDEKA BELAJAR DAN TEKNOLOGI MOBIL LISTRIK DI SMK NEGERI 1 NGAWEN GUNUNGKIDUL - Aan Yudianto; Herminarto Sofyan; Gunadi; Agus Widyianto; Supiningsih (Universitas Majalengka, 2022)
SMK Negeri 1 Ngawen as one of the leading vocational schools located in Gunungkidul, Special Region of Yogyakarta, requires strengthening of the implementation of the independent learning curriculum for SMK as a Center of Excellence and strengthening of electric car technology which is implemented in learning. This Off-Campus Lecturer Program aims to provide training to teachers at SMK Negeri 1 Ngawen in relation to strengthening the concept of independent learning and electric car technology in SMK which is applied in general learning related to strengthening hardskills, softskills, and character and harmony. between SMK and the world of work that is applied in learning in SMK. The target audience in this activity are teachers at SMK Negeri 1 Ngawen, Gunungkidul Regency, Special Region of Yogyakarta. The method of activities carried out in the Lecturer's Activities Outside the Campus is the lecture and discussion method accompanied by problem solving real problems that are expected by the school. This training activity has been carried out well. The results of the Evaluation Questionnaire showed that 65% strongly agree that the program is as needed, 76% strongly agree that the material provides benefits, 71% strongly agrees that the battery increases cooperation, 59% agrees that the program fosters independence, 59% strongly agrees that the delivery of material is clear and easy to understand, 65% of respondents strongly agree that the program encourages forward-looking, and 53% strongly agree that the results of the activities are in line with the expectations of the school.